Effect of Cr, Ni, Fe and Mn dopants on the performance of hydrothermal synthesized vanadium phosphate catalysts for n-butane oxidation - Yap, Taufiq Yun Hin; Theam, Kok Leong; Hutchings, Graham John; Dummer, Nicholas F.; Bartley, Jonathan K. (Taylor & Francis, 2010)
Vanadium phosphorus oxide (VPO) catalysts synthesized via hydrothermal method were introduced with some different dopants, Cr, Ni, Fe, and Mn during the preparation of the precursors, VOHPO4 · 0.5H2O. All modified precursors were subsequently transformed under reaction conditions to give the active phase, (VO)2P2O7. Several techniques were used to characterize the physicochemical properties of the catalysts, such as X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET), H2-temperature programmed reduction (TPR), laser Raman spectroscopy (LRS), and chemical analysis. The catalytic performance of the catalysts for selective oxidation of n-butane to maleic anhydride has been carried out by using a fixed bed microreactor (673 K, gas hourly space velocity [GHSV] = 2,400 hr-1). The results show that the addition of dopants into the VPO catalysts increased the surface area of the catalysts and induced the formation of V5+ phases as shown in XRD and LRS spectra that promoted the catalytic performance. A further water reflux treatment to all the precursors gave catalysts with only (VO)2P2O7 phase. However, the activity and selectivity of these catalysts were reduced markedly.